Multibeam bathymetry raw data (Kongsberg EM710 entire dataset) of RV METEOR during cruise M194 - Nico Augustin; Froukje M van der Zwan; Mia Schumacher (PANGAEA, 2024)
Raw multibeam bathymetry data were collected aboard RV METEOR during cruise M194 using a Kongsberg EM 710 multibeam echosounder. The expedition took place during 10.10.2023 - 07.11.2023 from Jeddah (Saudi) to Piraeus (Greece) in the Red Sea. The aim of the cruise in the frame of the extquotesingleHEXPLORES extquotesingle project aims to locate, study, and understand hydrothermal vent fields in the Red Sea Rift at accessible locations outside the brine pools. Data were recorded within the EEZ of Saudi Arabia. Sound velocity profiles (SVP) were applied on the data for calibration. Please see environmental data and the cruise report for details. The data are unprocessed and can therefore contain incorrect depth measurements (artifacts) if not further processed. Note that refraction errors may occur when no proper SVP is applied. Acquisition and provision of the data are part of the DAM Underway Project and published according to the FAIR principles.